paq'balth: The Klingon Epic - Schönfeld, Floris; Okrand, Marc; Ligtelijn, Kees; Van Gerven Oei, Vincent W.J (punctum books, 2011)
paq'batlh: The Klingon Epic is the definitive edition of the grand Klingon epic of the Kahless the Unforgettable (qeylIS lIjlaHbogh pagh). The story of Kahless is a tale of legendary proportions comparable to those of our own ancient heroes Hercules, Ulysses and Gilgamesh. Betrayed by his brother and witness to his father's brutal slaying, Kahless is pitted against his bitter enemy, the mighty tyrant Molor. To regain his honor he must travel into the Underworld, create the first bat'leth, and unite with his true love, Lady Lukara, to fight many epic battles. Through this awe-inspiring adventure Kahless redefines what its is to be truly Klingon. Reconstructed from several sources, this bilingual Klingon/English edition provides a keen insight into the nature of Klingon culture and mythology, and features the first publication of Ancient Klingon (no' Hol) fragments. Meticulously translated by the world's leading Klingon language expert, Marc Okrand, this classic epic is a must have for anyone interested in Klingon culture and language.